Copy number alternations of the 17q23-rs6504950 locus are associated with advanced breast cancers in Taiwanese women - Lin, Chien-Yu; Yang, Shu-Fen; Ho, Yu-Ling; Ho, Cheng-Mao (Ci ji yi xue za zhi, 2020)
Objective: Breast cancer is one of the most common malignancies and a leading cause of cancer-related death in women worldwide. Both hormone-related factors and genetic aberrations could cause breast cancer. We investigated copy number alternations (CNAs) on four breast cancer-susceptible loci, namely 2q35-rs13387042, 3p24-rs4973768, 17q23-rs6504950, and fibroblast growth factor receptor 2 (FGFR2)-rs2981578, in Taiwanese women. Patients and Methods: Breast cancer tissues and blood samples from 66 patients and their clinical data were collected from a human biobank. The copy numbers of the germline samples (from blood) and cancer tissues from each patient on the susceptible loci - 2q35, 3p24, 17q23, and FGFR2 - were obtained using TaqMan probes in the Applied Biosystems Inc., (ABI) StepOnePlus Real-Time Polymerase Chain Reaction instrument and CopyCaller® Software v1.0 (ABI, CA, USA). Results: The mean copy numbers output by CopyCaller® Software v1.0 of the cancer tissues on these susceptible loci (2q35, 3p24, 17q23, and FGFR2) from the 66 patients were higher than those of the blood samples (2.0 vs. 1.9); however, significantly higher copy numbers for cancer tissues compared with germline samples were discovered only on 2q35-rs13387042 (P = 0.035). In addition, patients with advanced breast cancers had relatively many CNAs between their cancer tissues and germline samples on 17q23-rs6504950 (P = 0.008). Multivariate analysis revealed that the risk factor for patients with advanced breast cancers was CNAs between cancer tissues and germline samples on 17q23-rs6504950 (odds ratio = 13.337, 95% confidence interval: 1.525-122.468). Conclusions: CNAs on 17q23-rs6504950 between cancer tissues and germline samples could affect cancer progression in Taiwanese women with breast cancer. Further investigations regarding the role of CNAs on 17q23-rs6504950 in cancer progression are necessary to elucidate the pathogenesis of breast cancer.